2020
DOI: 10.3390/ma13030766
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Machining Process of Titanium Ti6Al-4V Parts Manufactured by Wire Arc Additive Manufacturing (WAAM)

Abstract: In the current days, the new range of machine tools allows the production of titanium alloy parts for the aeronautical sector through additive technologies. The quality of the materials produced is being studied extensively by the research community. This new manufacturing paradigm also opens important challenges such as the definition and analysis of the optimal strategies for finishing-oriented machining in this type of part. Researchers in both materials and manufacturing processes are making numerous advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 21 publications
(27 reference statements)
2
19
0
Order By: Relevance
“…In addition, WAAM offers the possibility to create complex geometries, which allows the production of novel, lightweight structures [6]. Although, the manufactured parts exhibit surface roughness, which requires post processing with subtractive methods [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WAAM offers the possibility to create complex geometries, which allows the production of novel, lightweight structures [6]. Although, the manufactured parts exhibit surface roughness, which requires post processing with subtractive methods [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…An experiment test was performed on a substrate (10 mm thick base material) attached to the welding table. The manufacturing procedure is similar to that used by the authors in [16,17]. The graphical representation of the WAAM process is given in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The production of a wall with a homogeneous top surface is critical for the subsequent face milling process and obtaining the finished wall. In previous works, Veiga et al [27] have shown how face milling is a more critical machining process in this type of wall than tangential milling. The dimensions of the final wall will be determined by the minimum measured profile, shown in Figure 15, of the parabolic nature of the measured profiles; an effective wall of the rectangular cross-sectional area could be obtained.…”
Section: Analysis Of the Wall Geometrymentioning
confidence: 98%